ANALISIS IMPLEMENTASI LITERASI SAINS TERHADAP PEMBELAJARAN IPA SISWA KELAS IV SDN KARANGTENGAH 3 - Putri, Pramay Shella Arinda; Santi, Novi Nitya; Zaman, Wahid Ibnu (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the implementation of scientific literacy in science learning. A qualitative approach was used, with the research subjects being a fourth-grade teacher and students at SD Negeri Karangtengah 3. This approach was chosen because the data collected were in the form of a case study, specifically the implementation of scientific literacy. The research employed three instruments: interviews, documentation, and observation, with data analyzed using an interactive analysis technique. The conclusions of this study are: (1) scientific literacy helps students understand scientific concepts more effectively, making them more interested in learning science; (2) teachers play a crucial role in the application of scientific literacy, as they serve as the main facilitators who can guide, direct, and support students in understanding and applying scientific concepts; and (3) the impact of implementing scientific literacy on learning interest can be observed through several aspects, including improved comprehension, critical thinking skills, and relevance to everyday life.